CTNI-06. TRAM-01: A PHASE 2 STUDY OF TRAMETINIB FOR PATIENTS WITH PEDIATRIC GLIOMA WITH ACTIVATION OF THE MAPK/ERK PATHWAY. (12th November 2021) - Perreault, Sébastien; Larouche, Valérie; tabori, uri; Hawkins, Cynthia; Lippe, sarah; Ellezam, Benjamin; decarie, Jean-Claude; Ospina, Luis H; theoret, yves; Desjardins, Leandra; Metras, Marie-Elaine; Sultan, serge; et al.
Abstract: BACKGROUND: Pediatric low-grade gliomas (PLGG) are the most frequent brain tumors in children. It is known that the majority of PLGG have activation of the MAPK/ERK pathway. METHODS: This ongoing multicenter phase II trial includes three progressing/refractory PLGG groups: NF1 patients, KIAA1549-BRAF fusion patients and patients with other activation of the MAPK/ERK pathway (excluding V600E). The primary objective was to evaluate the overall response rate based on RANO criteria after daily oral trametinib administration for 18 cycles, lasting 28 days each. Secondary objectives include the assessment of progression-free survival, tolerability of trametinib, serum levels of trametinib and quality of life evaluation during treatment. RESULTS: As of February 12 2021, 50 patients have been enrolled (NF1: n=10; KIAA1549-BRAF fusion: n=31; other: n=9 including 5 patients with FGFR1 alterations). Median age is 8.8 years (range 2.4-25.5). Median follow-up is 17.5 months (range 4.7-28.5). Forty-three patients are evaluable. The overall response includes: 4 partial response (PR) (9%), 18 minor response (MR) (42%), 17 stable disease (40%), 4 progressive disease (9%). Median time to response is 5.5 months (range 2.4-13.8). Median duration of response is 6.1 months (range 0.6-26.5). Progression free survival at 12 months is 79.9% (95% CI 68.5-93.6%) and median progression free survival has not yet been reached. Treatment was discontinued for 30 patients: 16 after completing 18 cycles as planned, 5 for progressive disease, 5 for adverse events, 4 for other reasons. A total of 8 patients progressed after discontinuation of treatment including 6 patients (37.5%) that completed 18 cycles. Five of these patients had achieved minor response prior to discontinuation. CONCLUSION: Trametinib is a potentially effective targeted therapy for patients with recurrent/refractory PLGG. Treatment was overall well tolerated. This ongoing trial will continue to gather data on response rate, duration of response and safety of trametinib for PLGG.